PARTILHA DE INFORMAÇÃO EM CONTEXTO EMPRESARIAL NA ÓTICA DA CIÊNCIA DA INFORMAÇÃO - Moreira, D.; Martins, Susana; Carvalho, Milena (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2023)
In a business environment, meeting deadlines in projects can lead to the absence of information management, namely deficiencies in the process of creation and document organization that make it difficult to recover. The implemented project aims to define improvements in the processes of creation, organization and sharing of infodocumentation, leading to the development of instruments in this area. This is an applied investigation, based on the review of narrative literature and the collection of evidence using observation grids and their analysis. It is also exploratory-descriptive research, allowing to know and deepen themes. It was necessary to map the documentation produced throughout the developed projects and to an evaluation of the documentation stored in the institutional repositories. Improvements were proposed in the creation, organization and sharing of information documentation that used the technologies to facilitate the creation, access and dissemination of infodocumentation, thus fulfilling the proposed objective.